Association of uncoupling protein-2 -866G/A and Ala55Val polymorphisms with susceptibility to type 2 diabetes mellitus: A meta-analysis of case-control studies. Issue 6 (12th February 2021) - Xu, Lu; Chen, Shuyan; Zhan, Libin
Abstract: Background: Recently, the relationships between uncoupling protein-2 (UCP2) -866G/A ( rs659366 ) and Ala55Val ( rs660339 ) polymorphisms and the risk of type 2 diabetes mellitus (T2DM) have been explored considerably, but the results are greatly inconsistent. This meta-analysis was performed to further identify the association of UCP2 rs659366 and rs660339 with the risk of T2DM. Methods: Eligible studies were searched from PubMed, Embase, Cochrane Library, VIP database, Chinese National Knowledge Infrastructure, and Chinese WanFang database until March 8, 2020. The odds ratios with corresponding 95% confidence intervals (CIs), and P -values were used to assess the strength of the association. Results: A total of 26 studies were included in this study. UCP2 rs659366 was associated with the risk of T2DM in allele model (OR: 1.112, 95%CI: 1.009-1.224, P = 0.032), dominant model (OR: 1.189, 95%CI: 1.035–1.366, P = 0.014), and heterozygous model (OR: 1.177, 95%CI: 1.032–1.342, P = .015). A significantly increased risk of T2DM was detected in Asians by UCP2 rs659366 allele (OR: 1.132, 95%CI: 1.016–1.262, P = .025), dominant (OR: 1.218, 95%CI: 1.046–1.418, P = .011), homozygous (OR: 1.254, 95%CI: 1.022–1.540, P = .031) or heterozygous (OR: 1.198, 95%CI: 1.047–1.371, P = .009) models. There was no significant correlation between UCP2 rs660339 and the risk of T2DM ( P >.05). Conclusions: The UCP2 rs65366 is significantly associated with the risk of T2DM, especially in Asian population, while no evidence is found between the UCP2 rs660339 and the susceptibility to T2DM.